2015
DOI: 10.1063/1.4928034
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric nonequilibrium mini-plasma jet created by a 3D printer

Abstract: In this study, a small-sized plasma jet source with a 3.7 mm head diameter was created via a 3D printer. The jet’s emission properties and OH radical concentrations (generated by argon, helium, and nitrogen plasmas) were investigated using optical emission spectrometry (OES) and electron spin resonance (ESR). As such, for OES, each individual gas plasma propagates emission lines that derive from gases and ambient air inserted into the measurement system. For the case of ESR, a spin adduct of the OH radical is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…By contrast, a chemical scavenger is a compound that reacts with the reactive species in question and creates a new chemical compound.) These authors concluded that TPC was not selective for 1 O 2 and that other reactive oxygen species were contributing to the formation of the adduct [25]. In a different series of experiments, Zhu utilized TEMP in the presence of L-Histidine and 3-(10-(2-carboxy-ethyl)anthracen-9-Yl)-propionic acid (ADPA) as 1 O 2 scavengers [26].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, a chemical scavenger is a compound that reacts with the reactive species in question and creates a new chemical compound.) These authors concluded that TPC was not selective for 1 O 2 and that other reactive oxygen species were contributing to the formation of the adduct [25]. In a different series of experiments, Zhu utilized TEMP in the presence of L-Histidine and 3-(10-(2-carboxy-ethyl)anthracen-9-Yl)-propionic acid (ADPA) as 1 O 2 scavengers [26].…”
Section: Introductionmentioning
confidence: 99%
“…To fabricate a plasma jet body with a complex shape, a metal 3D printer was used. 3Dprinting technology has attracted increasing attention in manufacturing, including its use in plasma systems, due to its low cost and high flexibility [17][18][19]. Recently, a plasma jet for an endoscope with a diameter of approximately 3 mm produced by a metal 3D printer has been reported [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since most of the previously reported LTP devices were only able to produce LTP from argon (Ar) or helium (He), it would be difficult to use them to produce ROS and reactive nitrogen species stably in the gastrointestinal tract, which is an enclosed space. Takamatsu et al established a method for producing a smaller LTP source that can use various gases [22], and they succeeded in miniaturizing the tip of the plasma source (diameter: 3.7 mm) by using a 3D printer [23]. This new device can produce plasma not only from Ar and He, but also from oxygen (0 ), carbon dioxide (CO ), and nitrogen (N ).…”
Section: Introductionmentioning
confidence: 99%